Folklore, Analysis and Utilization of the Golden Cave and Silver Cave - Syafitri, Novia; Maulana, Muhammad Hanafi; Arraihan, Haddad Wifaq; Putri, Nezeliana; Prayitno, Nugroho Hadi; Harahap, Apriani (Universitas Syiah Kuala, 2023)
The Gold Cave and Silver Cave are tourist attractions located in Durian IV Mbelang Village, STM Hulu District, Deli Serdang Regency, North Sumatra. Based on the data obtained, the gold cave and silver cave save a lot of historical history. Even these caves have their own uniqueness, namely there are silver and gold grains at several points on the cave walls. The historical story and the uniqueness of the cave became the basis for conducting a study to uncover the scientific truth of the gold and silver cave in history and laboratory testing of the authenticity of the gold and silver. This study uses qualitative methods to describe and describe existing phenomena, both natural and human engineered. This method consists of several stages of research interviews and observations using data analysis model Miles and Huberma techniques and observations of recordings and research notes so that every information can be recorded properly. The results showed several legend stories and cave naming if in a hermeneutic perspective the legend stories and the names of the caves were made for the preservation of the cave and increasing the tourism of the cave. Laboratory tests proved the presence of particles resembling gold (Titanium Nitride compounds, Ti2N) and silveccr (Nickel Iron Oxid compounds, NiFe2O4).